MINIMIZATION OF CREDIT RISKS IN THE RURAL CREDIT UNION WITH THE USE OF SKORING SYSTEMS - Орлов, О. В. (Scientific Progress & Innovations, 2015)
The article deals with the problem of credit risk in the rural credit unions and we offer an effective system of risk assessment using the scoring system. Theoretical sources of scoring as the scientific method are adduced. Specific offers for the development and application of scoring in the rural credit unions are given. We emphasize the importance and the need to use this method in practical activities of these organizations, the feasibility of developing of a single model of an automated credit scoring system in order to minimization of credit risk in the rural credit unions.